2021
DOI: 10.5603/cj.a2019.0085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term radial artery occlusion following trans-radial coronary intervention using 6-french versus 7-french sheaths

Abstract: Background: The aim of this study was to explore the impact of 6-Fr and 7-Fr sheaths on the incidence of long-term radial artery occlusion (RAO) after trans-radial coronary intervention (TRI). , patients with ischemic heart disease including acute myocardial infarction and true bifurcation lesions were randomly assigned to 6-Fr group and 7-Fr group immediately after coronary angiography in a 1:1 ratio. The radial artery diameters were observed by ultrasound examination one day prior to TRI as well as at 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…From this, the authors conclude that using the two‐bladder band, operators can safely use larger sheaths for complex interventions without increasing RAO rates. However, a similar finding was reported previously with conventional patent hemostasis technique (without ulnar compression) 5 . Thus, the equivalent rates of RAO for 6 French versus 7 French sheaths may not be attributable or unique to the two‐bladder band.…”
Section: Author Journal Date Study Design Study Hypothesis Finding Co...supporting
confidence: 86%
See 1 more Smart Citation
“…From this, the authors conclude that using the two‐bladder band, operators can safely use larger sheaths for complex interventions without increasing RAO rates. However, a similar finding was reported previously with conventional patent hemostasis technique (without ulnar compression) 5 . Thus, the equivalent rates of RAO for 6 French versus 7 French sheaths may not be attributable or unique to the two‐bladder band.…”
Section: Author Journal Date Study Design Study Hypothesis Finding Co...supporting
confidence: 86%
“…However, a similar finding was reported previously with conventional patent hemostasis technique (without ulnar compression). 5 Thus, the equivalent rates of RAO for 6 French versus 7 French sheaths may not be attributable or unique to the two-bladder band.…”
mentioning
confidence: 98%
“…In a Japanese study using Ultrasound Doppler assessment of the radial artery, the S/A ratio >1 was associated with lower blood flow in radial artery after TRI, but the association with RAO has not been confirmed [28]. In addition, Fan et al [16] found that the 7-Fr sheaths were related with a greater incidence of RAO in 248 participants randomized to 6-Fr or 7-Fr sheaths (5.71% vs. 7.34%, p < 0.01). In our study, multivariate regression analysis showed that several baseline characteristics associated with an increased risk of RAO, such as lower BMI, peripheral artery disease and higher S/A value.…”
Section: Discussionmentioning
confidence: 93%
“…32 Recently, a randomized controlled clinical trial compared the impact of 6-Fr and 7-Fr sheaths on the incidence of long-term RAO, and found that there was a non-significant difference in the incidence of RAO at 1-year after TRI (8.57% vs. 12.84%, p = .313). 33 Preventing RAO is of utmost clinical importance and should be a central consideration. 6,7,34 It is important to note that the RAO rate is dependent on the timing of the evaluation, with significantly higher rates for earlier assessments than for later assessments (generally at 1 month).…”
Section: T a B L E 3 Access-site Complicationsmentioning
confidence: 99%
“…In a small singlecenter randomized trial, Fan et al showed that compared to 6-Fr sheath, 7-Fr sheath did not increase short-term or long-term incidence of RAO after TRI in patients with ischemic heart disease including acute myocardial infarction and true bifurcation lesions. 33 The rate of radial artery occlusion between the 7-Fr Glidesheath Slender (Terumo, Japan)…”
Section: T a B L E 3 Access-site Complicationsmentioning
confidence: 99%